2021
DOI: 10.1007/s12371-021-00643-y
|View full text |Cite
|
Sign up to set email alerts
|

Principles for Developing a National Soil Heritage Inventory

Abstract: Geoconservation has gained a growing recognition in the last three decades. Significant steps have been given to identify, assess, and protect many geosites worldwide. Several countries have published national geosite inventories but quite often soils are not included in these inventories. Consequently, soils are usually disregarded in geoconservation strategies, in spite of they are geodiversity elements with different types of values that support crucial ecosystem services. Soils have multiple functions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…1), and Amazon Forest since the 20th century. To better use and preserve these environments, it is necessary to know and understand their pedodiversity and its values (Botelho and Brilha, 2022) also through an integrated approach (Paula Silva et al, 2021;Garcia et al, 2022).…”
Section: The Complex Relationship Between Food Security and Environme...mentioning
confidence: 99%
“…1), and Amazon Forest since the 20th century. To better use and preserve these environments, it is necessary to know and understand their pedodiversity and its values (Botelho and Brilha, 2022) also through an integrated approach (Paula Silva et al, 2021;Garcia et al, 2022).…”
Section: The Complex Relationship Between Food Security and Environme...mentioning
confidence: 99%
“…A pedosite was defined by Costantini and L'Abate [10] (p. 143) as a "georeferenced soil having cultural heritage, that is, a soil exposure or a soilscape where an extraordinary cultural interest has been recognised [11]". More recently, following the Brilha [8] approach applied for the geosites, Bothelo and Brilha [12] suggested that the term pedosite should be restricted to soil with high scientific value. Whereas, similarly to the geodiversity sites, the "sites of potential pedological interest" indicate those soils with no particular scientific relevance, but with educational, touristic, or other values [9].…”
Section: Introductionmentioning
confidence: 99%
“…An understanding of geoheritage could contribute to knowledge on geological and geomorphological characteristics, education, and public awareness on geoconservation and landscape protection issues. Moreover, the study of geosites promotes the process of developing laws on this topic, and the creation of databases useful for a better knowledge and conservation of geological heritage [9,10].…”
Section: Introductionmentioning
confidence: 99%